2017
DOI: 10.3390/ijms18091908
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phenethyl Isothiocyanate Protects Mice from Colitis Associated Colon Cancer

Abstract: We have previously reported alleviation of dextran sodium sulfate (DSS)-induced ulcerative colitis signs in phenethyl isothiocyanate (PEITC)-treated mice. Here we investigated chemoprotective activities of PEITC in mice with Azoxymethane-DSS induced colitis associated colon carcinogenesis. We also examined the molecular mediators associated with the PEITC effects using relevant cell lines. A 0.12% PEITC-enriched mouse-diet reduced mucosal and submucosal inflammation as well as glandular atypia by 12% and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Induction of mitochondria caspase cascade and JNK, critical factors for the initiation of apoptotic was observed in PEITC treated HT-29, colon cancer cell [ 82 ]. Anti-inflammatory effect of PEITC against colon cancer was correlated with the lesser expression of NF-κB [ 83 ].…”
Section: Molecular Mechanism Of Itcs In Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of mitochondria caspase cascade and JNK, critical factors for the initiation of apoptotic was observed in PEITC treated HT-29, colon cancer cell [ 82 ]. Anti-inflammatory effect of PEITC against colon cancer was correlated with the lesser expression of NF-κB [ 83 ].…”
Section: Molecular Mechanism Of Itcs In Cancer Preventionmentioning
confidence: 99%
“…These results suggest that the interference of β-catenin binding on the TBE0 site by p65 is involved in the suppression of cyclin D1 gene expression [ 134 ]. BITC significantly enhanced the nuclear translocation and increased the sensitivity of NF-κB [ 83 ]. Further, Liu and Dey (2010) reported that PEITC inhibits NF-κB in a concentration-dependent manner.…”
Section: Direct and Indirect Inhibition Of Nf-κb By Itcsmentioning
confidence: 99%
“…Recent epidemiologic studies show that utilization of cruciferous foods can reduce the event of a threat and diminish the frequency of malignant growth [1,2]. For instance, the intake of cruciferous vegetables helps to reduce the risk of ovarian [3] and colon cancer [4,5], lung cancer [6], and prostate cancer [7,8]. Cruciferous vegetables are in the Brassicaceae family that includes broccoli, cabbage, wasabi, mustard cauliflower, horseradish, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Phenethyl isothiocyanate (PEITC) is a biologically active dietary compound that is derived from cruciferous vegetables, such as watercress, broccoli, cabbage, and cauliflower [ 28 , 29 ]. We and others have reported anti-inflammatory and chemo-preventive characteristics of PEITC [ 29 , 30 , 31 , 32 , 33 , 34 ]. More recently, we showed that PEITC targets CSCs by promoting apoptosis [ 34 ].…”
Section: Introductionmentioning
confidence: 99%